Theta Burst TMS over the Pre-SMA Improves Inhibitory Control in Gambling Disorder Subjects as Assessed with Stop Signal Task - Gioele Gavazzi; Carlo Cavaliere; Marco Salvatore; Nikolaos Makris; Stefano Pallanti (Brain Sciences)
Background. Inhibitory control failure represents a central trait in substance and behavioral addictions, which includes patients affected with gambling disorder (GD). In GD patients, research on this trait of the addiction cycle has primarily focused on the use of pharmacological treatments for its assessment. More recently, modification of neural activity using transcranial magnetic stimulation (TMS) has been used to explore the dimensions of GD using patient questionnaires. Methods. Herein, we evaluated the use of continuous Theta burst stimulation (cTBS) over the pre-supplementary motor area (pre-SMA) to determine if it modified inhibitory control in the stop signal task of patients affected by GD when compared with a group of healthy controls without cTBS treatment. Results. To the best of our knowledge, our study is the first to report that TMS treatment of GD patients is associated with a behavioral improvement of stop signal reaction time. Conclusion. Our results suggest that this TMS-mediated improvement in the efficiency of inhibitory control in GD patients warrants further mechanistic studies in a larger cohort to determine if can be used as a treatment modality.